MET and PTEN gene copy numbers and Ki-67 protein expression associate with pathologic complete response in ERBB2-positive breast carcinoma patients treated with neoadjuvant trastuzumab-based therapy. Issue 1 (December 2016) - Calhoun, Benjamin; Portier, Bryce; Wang, Zhen; Minca, Eugen; Budd, G.; Lanigan, Christopher; Tubbs, Raymond; Morrison, Larry
Abstract Background Pathologic complete response (pCR) after neoadjuvant chemotherapy for breast cancer is associated with improved prognosis in aggressive tumor subtypes, including ERBB2- positive tumors. Recent adoption of pCR as a surrogate endpoint for clinical trials in early stage breast cancer in the neoadjuvant setting highlights the need for biomarkers that, alone or in combination, help predict the likelihood of response to treatment. Methods Biopsy specimens from 29 patients with invasive ductal carcinoma treated with trastuzumab-based therapy prior to definitive resection and pathologic staging were evaluated by dual color bright field in situ hybridization (dual ISH) using probes forMET, TOP2A, PTEN, andPIK3CA genes, each paired with centromeric probes to their respective chromosomes (chromosomes 7, 17, 10, and 3). Ki-67 expression was assessed by immunohistochemistry (IHC). Various parameters describing copy number alterations were evaluated for each gene and centromere probe to identify the optimal parameters for clinical relevance. Combinations of ISH parameters and IHC expression for Ki-67 were also evaluated. Results Of the four genes and their respective chromosomes evaluated by ISH, two gene copy number parameters provided statistically significant associations with pCR:MET gain or loss relative to chromosome 7 (AUC = 0.791, sensitivity = 92 % and specificity = 67 % at optimal cutoff, p = 0.0032) and gain ofPTEN (AUC = 0.674, sensitivity = 38 % and specificity = 100 % at optimal cutoff, p = 0.039). Ki-67 expression was also found to associate significantly with pCR (AUC = 0.726, sensitivity = 100 % and specificity = 42 % at optimal cutoff, p = 0.0098). Combining gain or loss ofMET relative to chromosome 7 with Ki-67 expression further improved the association with pCR (AUC = 0.847, sensitivity = 92 % and specificity = 83 % at optimal cutoffs, p = 0.0006). Conclusions An immunogenotypic signature of low complexity comprisingMET relative copy number and Ki-67 expression generated by dual ISH and IHC may help predict pCR in ERBB2-positive breast cancer treated with neoadjuvant chemotherapy and trastuzumab. These findings require validation in additional patient cohorts.